The truth of the matter: truth finding in Victorian sensation fiction - Goh, Hillary Anqi (Nanyang Technological University, 2023)
This dissertation seeks to evaluate how Victorian sensation fiction engages with means of truth finding and systematic inquiry through aesthetic and scientific discourse of the time. With the introduction of new and influential scientific studies, the authority of religion and prior metaphysical certainties of knowledge were increasingly undermined in the Victorian period, setting the stage for redefining knowing and the knowable in order to address existential questions. This process of re-evaluating past knowledge and the pursuit of truth can be seen in the genre of sensation fiction, which experimented with ideas of suspense and inquiry through mystery arcs based on the sensationalised crimes of the day. Setting up intriguing mystery plots only to conclude with scandalous revelations within the typically safe domestic space articulates the changing Victorian outlook of how things were not as they seem. Nevertheless, the elements of the aesthetic and the scientific within these texts contribute to shedding light and resolving these mysteries. I propose analysing sensation fiction which explicitly engages with current aesthetic or scientific theories as methods of uncovering the truth. These texts include M.E Braddon’s Lady Audley’s Secret (1862) and Wilkie Collins’ The Moonstone (1868) of the mid-nineteenth century to the later part of the century with Collins’ Heart and Science (1882). A critical analysis of these texts shows how the evolution of aesthetic and scientific discourse work to reveal not just the truths of mysteries, but ultimately the conceptions and realisations of the nature of Man at the heart of these mysteries.